Produktivitas Usahatani Jamur Tiram Putih Berdasarkan Segmentasi Usaha Di Kabupaten Ciamis, Jawa Barat - Eli Ukiwa; Suhartono Suhartono (Fakultas Kehutanan Universitas Mulawarman, 2020)
White oyster mushroom cultivation has been widely recognized by the people in Ciamis Regency on a small or large scale. However, this farming phenomenon experienced many ups and downs. Though the need for mushroom consumption by the market is still quite high. This study aims to determine the extent to which the productivity differences of white oyster mushroom farming are cultivated by farmers in three different business segments and how is the business feasibility. The method used in this study is a survey method. Data were collected through interviews with purposive sampling to mushroom farmers. To find out the productivity and feasibility of farming, a cost, and income analysis approach and R/C. Then a different test is conducted to determine the differences in income between business segments. The results showed that the farming of white oyster mushrooms in the three business segments can generate different incomes. The business segment from baglog to harvest has the highest productivity (R/C 1,16). However, the highest income is generated by white oyster mushroom farming in the baglog manufacturing segment. Financially the three segments of white oyster mushroom farming are feasible because they can generate positive income and R/C>1